Lucas Davenport : Masked Prey - Book 30 - Sandford, John, 1944 February 23-; Ferrone, Richard (New York, NY : Penguin Audio, an imprint of the Penguin Random House Audio Publishing Group, 2020)
The daughter of a US Senator is monitoring her social media presence when she finds a picture of herself on a strange blog. And there are other pictures of the children of other influential Washington politicians, walking or standing outside their schools, each identified by name. Surrounding the photos are texts of vicious political rants from a motley variety of extremist groups. The anonymous photographer can't be pinned down to one location or IP address, and more importantly, at least to the paper-processing bureaucrats, no crime has actually been committed. With nowhere else to turn, influential senators decide to call in someone who can operate outside the FBI's constraints: Lucas Davenport.
Keywords: Davenport, Lucas -- (Fictitious character) -- Fiction; Photographs -- Fiction; Social media -- Fiction; Politicians -- Fiction -- United States; Political fiction; Thrillers (Fiction); Detective and mystery fiction; Audiobooks